SAFEGUARDING HORMANI BROTHERS AND SISTERS AND CARRYING OUT LEGAL PROTECTION AGAINST ECOSYSTEM CONSERVATION IN MALUKU - La Ode Angga La Ode Angga (Cepalo, 2020)
Brothers and Sisters of people in Maluku have the same hopes and ideals to always maintain peace in the land of the Kings of this Country. Harmony that is manifested in togetherness, friendship, brotherhood, love between fellow children in Maluku, and the silatu of the womb. It will motivate high civilization between public and indigenous people value if Brothers and Sisters of Maluku maintain peace that will ensure harmony among people. On the other hand, it will preserve ecosystems in Maluku which will create Harman between humans and the environment. This research explains the forms of basudara people’s activities as a form of implementation of peace preservation. This study uses a normative legal approach; normative legal research is carried out using appropriate methods based on the scientific characteristics of legal science. Moreover, this study discusses harmony maintenance of brothers in Maluku that perform Legal Protection against Ecosystem Conservation in Maluku. The research finds that the one form of keeping peace in Maluku is in the form of togetherness, friendship, brotherhood and love. It is believed that these principles will provide positive energy in humanity welfare. Therefore, the Government of Maluku must encourage awareness of both general public and indigenous people of Maluku.